Portfolio Optimization of Technology Companies in Malaysia: An Application of Fuzzy TOPSIS-Mean-Absolute Deviation Approach - Siew, Lam Weng; Jaaman, Saiful Hafizah; Hoe, Lam Weng (International Journal of Industrial Engineering, Technology & Operations Management, 2023)
Selecting and weighting the companies are the main processes in portfolio optimization. It is important to select and determine the companies' weights in constructing the optimal portfolio. In this paper, we propose a two-phase Mean-Absolute Deviation (MAD) model in portfolio optimization of technology companies in Malaysia. In the first phase, the companies’ financial performance is determined and ranked with Fuzzy Technique for Order of Preference by Similarity to the Ideal Solution (TOPSIS). Selection of the good financial performance companies can minimize the influence of firm-specific risk in minimizing the risk of the portfolio at the expected return. In the second phase, the optimal portfolio is generated by weighting the selected companies with MAD model. The results indicate that the investors can minimize the portfolio risk to achieve the expected return with the two-phase MAD model. The significance of this paper is to contribute to the development of portfolio optimization by integrating the Fuzzy TOPSIS and MAD approaches.